The Synergistic Role of Integrated Computed Tomography and Magnetic Resonance Cholangiopancreatography in Disorders of the Pancreatobiliary System - Santosh Rai; Saubhagya Srivastava; Sandeep Gopal; Anika Tiku (Thieme Medical and Scientific Publishers Pvt. Ltd., 2024)
Objective The aim of the study was to evaluate the synergistic role and advantages of integrating noncontrast computed tomography (NCCT) and magnetic resonance cholangiopancreatography (MRCP) in disorders of the pancreatobiliary (PB) system.